ATF3 deficiency in chondrocytes alleviates osteoarthritis development. Issue 4 (14th June 2016) - Iezaki, Takashi; Ozaki, Kakeru; Fukasawa, Kazuya; Inoue, Makoto; Kitajima, Shigetaka; Muneta, Takeshi; Takeda, Shu; Fujita, Hiroyuki; Onishi, Yuki; Horie, Tetsuhiro; Yoneda, Yukio; Takarada, Takeshi; et al.
Abstract: Activating transcription factor 3 (Atf3) has been implicated in the pathogenesis of various diseases, including cancer and inflammation, as well as in the regulation of cell proliferation and differentiation. However, the involvement of Atf3 in developmental skeletogenesis and joint disease has not been well studied to date. Here, we show that Atf3 is a critical mediator of osteoarthritis (OA) development through its expression in chondrocytes. ATF3 expression was markedly up‐regulated in the OA cartilage of both mice and humans. Conditional deletion of Atf3 in chondrocytes did not result in skeletal abnormalities or affect the chondrogenesis, but alleviated the development of OA generated by surgically inducing knee joint instability in mice. Inflammatory cytokines significantly up‐regulated Atf3 expression through the nuclear factor‐kB (NF‐kB) pathway, while cytokine‐induced interleukin‐6 ( Il6 ) expression was repressed, in ATF3‐deleted murine and human chondrocytes. Mechanistically, Atf3 deficiency decreased cytokine‐induced Il6 transcription in chondrocytes through repressing NF‐kB signalling by the attenuation of the phosphorylation status of IkB and p65. These findings suggest that Atf3 is implicated in the pathogenesis of OA through modulation of inflammatory cytokine expression in chondrocytes, and the feed‐forward loop of inflammatory cytokines/NF‐kB/Atf3 in chondrocytes may be a novel therapeutic target for the treatment for OA. Copyright © 2016 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.